O desenvolvimento da Lingüística Textual no Brasil - Koch, Ingedore G. Villaça (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2018)
The scope of this paper is to present a critical review of what has been done in the field of Textlinguistics, mainly in Brazil, in the second half of the century and to point out some of the perspectives for new developments in this area.